A solar and wind driven energy system for hydrogen and urea production with CO2 capturing. (22nd January 2021) - Ishaq, Haris; Siddiqui, Osamah; Chehade, Ghassan; Dincer, Ibrahim
Abstract: A novel solar PV and wind energy based system is proposed in this study for capturing carbon dioxide as well as producing hydrogen, urea and power. Both Aspen Plus and EES software packages are employed for analyses and simulations. The present system is designed in a way that PEM electrolyzer is powered by the wind turbines for hydrogen production, which is further converted into ammonia and then synthesizes urea by capturing CO2 and additional power is supplied to the community. The solar PV is employed to power the cryogenic air separation unit and the additional power is used for the industrial purpose. In the proposed system, ammonia does not only capture CO2 but also synthesizes urea for fertilizer industry. The amount of electrical power produced by the system is 2.14 MW. The designed system produces 518.4 kmol/d of hydrogen and synthesizes 86.4 kmol/d of urea. Furthermore, several parametric studies are employed to investigate the system performance. Highlights: A novel solar-wind hybrid energy system is developed for hydrogen and urea production. Produced hydrogen is converted into ammonia and synthesizes urea by capturing CO2. The amount of electrical power produced by the system is 2.14 MW. Designed system produces 518.4 kmol/d of H2 and synthesizes 86.4 kmol/d of urea.